2022
DOI: 10.1097/scs.0000000000008799
|View full text |Cite
|
Sign up to set email alerts
|

One Patient of Blepharoptosis Caused by Levator Palpebrae Superioris Aponeurosis Degeneration

Abstract: Ptosis is one of the common diseases of plastic surgery, which is caused by various causes of levator palpebrae superioris dysfunction or Müller muscle insufficiency, which is manifested by the upper eyelid margin being lower than normal when level viewed. Ptosis can be divided into congenital and acquired, and the main cause of congenital ptosis is due to congenital levator palpebrae superioris dysplasia or the motor nerve innervation that innervates it is caused by abnormal oculomotor neurodevelopment and dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Recent research suggests that oculomotor nerve palsy caused by pyraclostrobin may share similar mechanisms with botulinum toxin-induced muscle paralysis, where the toxin absorbs through the conjunctiva and enters the gap between the Muller muscle and the levator palpebrae superioris synapses, inhibiting the release of acetylcholine from the presynaptic membrane of motor nerve endings, causing flaccid paralysis of the muscles. [ 13 ] Alternatively, the toxin may act on acetylcholine receptors, preventing acetylcholine from binding to acetylcholine receptors, leading to paralysis of the muscles innervated by the oculomotor nerve. Regarding the neurotoxicity of pyraclostrobin, researchers have found that it can induce neurotoxicity in rats by blocking acetylcholinesterase activity and reducing dopamine, serotonin, and γ-aminobutyric acid levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that oculomotor nerve palsy caused by pyraclostrobin may share similar mechanisms with botulinum toxin-induced muscle paralysis, where the toxin absorbs through the conjunctiva and enters the gap between the Muller muscle and the levator palpebrae superioris synapses, inhibiting the release of acetylcholine from the presynaptic membrane of motor nerve endings, causing flaccid paralysis of the muscles. [ 13 ] Alternatively, the toxin may act on acetylcholine receptors, preventing acetylcholine from binding to acetylcholine receptors, leading to paralysis of the muscles innervated by the oculomotor nerve. Regarding the neurotoxicity of pyraclostrobin, researchers have found that it can induce neurotoxicity in rats by blocking acetylcholinesterase activity and reducing dopamine, serotonin, and γ-aminobutyric acid levels.…”
Section: Discussionmentioning
confidence: 99%